A large biatrial thrombus entrapped by patent foramen ovale in a case with massive pulmonary embolism - Derviş, Emir (Turk Gogus Kalp Damar Cerrahisi Derg, 2018)
Thrombus development in cardiac chambers increases the risk of mortality, compared to pulmonary embolism alone, and can require change in therapy. In the presence of patent foramen ovale, paradoxical systemic embolization can occur associated with a higher incidence of death and embolic complications. Herein, we present a case of pulmonary embolism concomitant a right atrial huge thrombus entrapped in patent foramen ovale and prolapsing into the left heart chambers.